Antiobesity Activity Of A Combination Of Extracts From Porang Tubers ( Amorphopallus Muelleri ) and Jati Belanda Leaves ( Guazuma Ulmifolia ) In Obesity Rat Models - Fahmi, Muhammad Zaini; Muhtadi; Hidayatullah, Muhammad Haqqi (Universitas Muhammadiyah Surakarta, 2024)
Obesity is an excessive accumulation of fat due to an imbalance in energy intake with energi expenditure for a long time. Obesity can be reduced by taking drugs. One of the commonly used herbal medicines for obesity is porang tubers and Dutch teak plants. The purpose of this study was to prove the anti-obesity activity of the combination of porang tuber extract with Dutch teak leaf extract in obese rat models. Anti-obesity effect test was carried out for 14 days on obese rats. The antiobesity effect was assessed by the index Lee ≥ 0,3 and weight loss. This study was conducted using 5 groups of test animals, namely the negative group (PGS 1%), positive (orlistat 7.57 mg/kgBW), and 3 groups of a combination of porang tuber extract and Dutch teak leaves, 50 + 62.5; 50 + 125; 50 + 250 mg/kgBW. Weight loss occurred in groups II, IV,and V, in groups I there was an increase in body weight. The mean results of the Lee index of groups I, II, III, IV, and V were 0,31 ± 0,02, 0,29 ± 0,01, 0,29 ± 0,01, 0,29 ± 0,01, and 0,30 ± 0,01. Data analysis using the Kruskall-Wallis test resulted in no significant difference of 0.715 (p>0.05) on day 14 which showed that the combination of porang tubers and Dutch teak leaves had no anti-obesity effect.